Money function in the adventure novel “Money, Cuba and Literature” by Oleg Galetka (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article investigates the function of money in the writerʼs life. This paper represents the attempt to determine the money influence, its dependence and attachment to the person of the word art. It also describes the consequences of writing fiction works for money on the writerʼs state of mind. In addition, the article defines the level of economic consciousness of the characters. Moreover it studies the role of money in the life of characters from different social strata. It is noted that the attitude of the characters to money also performs their characterizing function. Some characters in the novel “Money, Cuba and Literature” choose money as a tool for lifestyles. They buy love, freedom, works of art, and relatives for money. The word “money”, which is relevant in the title, takes a strong position in the text of the novel. It is shown that the value of the writer’s labor is determined by the amount of money spent by the tycoon’s daughter in a week. Money performs its economic function of value standard in the novel.
Keywords: money; writer; art; literature; economic consciousness; value standard; lifestyle